2013
DOI: 10.1080/13632752.2012.675132
|View full text |Cite
|
Sign up to set email alerts
|

Reducing subjectivity in special education referrals by educators working with Latino students: using functional behavioral assessment as a pre-referral practice in student support teams

Abstract: Over the past several decades, the Latino population throughout the USA has demonstrated significant growth and exceeded that of other ethnic minority groups. This influx is particularly evident in the student enrollment of US schools as the number of Latino students has increased by approximately 10 million within the past 10 years. With this dramatic increase, there are a number of critical issues that present significant barriers to a high-quality educational experience for Latino students, specifically ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…From the 1st week of the semester, students are introduced to the importance of considering and respecting cultural norms and differences throughout the entire assessment process. They are assigned two readings (i.e., Moreno et al, 2014;Moreno & Gaytán, 2013) and are required to write a response regarding the importance of considering culture within the FBA process, including a discussion of the changing demographics within the United States, current issues regarding the disproportionate use of disciplinary actions with students from different races, recommendations/strategies for decreasing educator biases and other issues, and an application to the students' own clinical work. Students are also encouraged to share their own personal experiences of working with clients from different backgrounds within the weekly discussion boards.…”
Section: Course Illustrationmentioning
confidence: 99%
“…From the 1st week of the semester, students are introduced to the importance of considering and respecting cultural norms and differences throughout the entire assessment process. They are assigned two readings (i.e., Moreno et al, 2014;Moreno & Gaytán, 2013) and are required to write a response regarding the importance of considering culture within the FBA process, including a discussion of the changing demographics within the United States, current issues regarding the disproportionate use of disciplinary actions with students from different races, recommendations/strategies for decreasing educator biases and other issues, and an application to the students' own clinical work. Students are also encouraged to share their own personal experiences of working with clients from different backgrounds within the weekly discussion boards.…”
Section: Course Illustrationmentioning
confidence: 99%
“…Furthermore, studies have demonstrated that functional assessment methodology is relevant for diverse ages, ranging from preschool (e.g., Duda, Dunlap, Fox, Lentini, & Clarke, 2004) through adolescence (e.g., Radford & Ervin, 2002; Turton, Umbreit, Liaupsin, & Bartley, 2007). In addition, cross-cultural applications suggest that functional assessment is an adaptable process responsive to differing values and social practices (Baba & Tanaka-Matsumi, 2011; Cho Blair, Umbreit, Dunlap, & Jung, 2007; Moreno & Gaytán, 2013; Theodoridou & Koutsoklenis, 2013; Turton et al, 2007). Finally, researchers have directly compared the effects of intervention that is function-derived with nonfunction-derived intervention, demonstrating the superiority of interventions linked to behavioral function (Ingram, Lewis-Palmer, & Sugai, 2005; Newcomer & Lewis, 2004; Payne, Scott, & Conroy, 2007).…”
Section: What We Have Learnedmentioning
confidence: 99%
“…Therefore, members should be selected carefully according to the needs of each school and its population. When working with ethnically diverse youth, special consideration must be taken to ensure that an individual who is knowledgeable about the student culture and culturally responsive practices participates in the team (Moreno & Gaytán, 2013). A primary responsibility of this individual is to help determine whether a referral is reflective of true social, emotional, or behavioral difficulties or is related to cultural issues in the classroom.…”
Section: The Prereferral Teammentioning
confidence: 99%
“…Practitioners may wish to consider the perception of school and mental health services that a family is likely to have, and they should be aware that students' families might express different views on mental illness that must be respected. School personnel must also strive to be aware of environmental stressors affecting the involvement of families in the assessment process and be understanding when difficulties arise (Moreno & Gaytán, 2013). Finally, the cultural background of the interviewer is also important to consider, particularly when a rift is suspected between the interviewer's perspective and the perspective of the student, teacher, or family.…”
Section: Clinical Interviewmentioning
confidence: 99%